Step
*
1
1
1
1
1
1
1
of Lemma
better-r2-straightedge-compass
1. a : ℝ^2
2. b : ℝ^2
3. b ≠ a
4. x : ℝ
5. λi.if (i =z 0) then |x| + r1 else r0 fi - λi.r0⋅λi.if (i =z 0) then |x| + r1 else r0 fi - λi.r0
= ((|x| + r1) * (|x| + r1))
⊢ rsqrt(λi.if (i =z 0) then |x| + r1 else r0 fi - λi.r0⋅λi.if (i =z 0) then |x| + r1 else r0 fi - λi.r0) = (|x| + r1)
BY
{ (RWO "-1" 0 THEN Auto) }
Latex:
Latex:
1. a : \mBbbR{}\^{}2
2. b : \mBbbR{}\^{}2
3. b \mneq{} a
4. x : \mBbbR{}
5. \mlambda{}i.if (i =\msubz{} 0) then |x| + r1 else r0 fi - \mlambda{}i.r0\mcdot{}\mlambda{}i.if (i =\msubz{} 0) then |x| + r1 else r0 fi - \mlambda{}i.r0
= ((|x| + r1) * (|x| + r1))
\mvdash{} rsqrt(\mlambda{}i.if (i =\msubz{} 0) then |x| + r1 else r0 fi - \mlambda{}i.r0\mcdot{}... - \mlambda{}i.r0)
= (|x| + r1)
By
Latex:
(RWO "-1" 0 THEN Auto)
Home
Index